ISLAMIC FASHION TREND PHENOMENON IN SEMARANG OLD CITY AREA - Pranoto, Pranoto; Dwijaningtyas, Srinata; Livansyah, Angel; Khotimah, Kusnul; Trisnanda, Raviendo; Najmuddin, Najmuddin (Universitas Mathla’ul Anwar Banten, 2024)
Tourism in Semarang's Old Town is a phenomenon that has a significant impact on tourists' dress preferences. This article presents an observational analysis of how age, economy, and culture influence tourists' dress choices in the context of Semarang's Old Town. The research method used is an ethnographic approach involving in-depth observations, interviews, and active participation in the traveller community. The results revealed age variations among tourists, with young people and older generations visiting. The implications of age are reflected in dress preferences, with the younger generation being more experimental in Islamic fashion styles, while the older generation is more conservative. Economic characteristics also play an important role, with high-income travellers opting for luxury clothing while low-income ones opt for more modest clothing. The influence of Islamic values creates diversity in clothing choices, with visitors who identify themselves as Muslims more likely to choose clothing in accordance with Islamic teachings. A sense of respect for a particular culture also influences clothing choices. In conclusion, tourists' dress preferences in Semarang's Old Town are reflected through a complex interaction between age, economy, Islamic values, and culture. Knowledge of these factors is important in the development of inclusive and sustainable tourism experiences.